2016
DOI: 10.2337/dcs15-3009
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of DPP-4 Inhibitors Associated With an Increased Risk for Heart Failure? Lessons From EXAMINE, SAVOR-TIMI 53, and TECOS

Abstract: About 40 years ago, the Framingham study first documented that the risk for heart failure (HF) in patients with diabetes was about twofold higher in men and fivefold in women compared with individuals without diabetes (1). The UK Prospective Diabetes Study (UKPDS) reported that the incidence of hospital admission for HF was similar to that of nonfatal myocardial infarction and nonfatal stroke (2). A more recent 6-year follow-up study of 65,619 patients with type 2 diabetes treated with insulin reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…However, in another large RCT, the TECOS study, sitagliptin did not increase the rate of hospitalization for HF in T2DM patients with established cardiovascular disease: HR 1.00 (95% CI: 0.83–1.20) 26 . In a small RCT, the VIVIDD Trial, vildagliptin usage in T2DM patients with established HF did not worsen HF 21 . A recent meta-analysis showed that there is only weak evidence for an increased risk of HF with gliptin usage 27 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in another large RCT, the TECOS study, sitagliptin did not increase the rate of hospitalization for HF in T2DM patients with established cardiovascular disease: HR 1.00 (95% CI: 0.83–1.20) 26 . In a small RCT, the VIVIDD Trial, vildagliptin usage in T2DM patients with established HF did not worsen HF 21 . A recent meta-analysis showed that there is only weak evidence for an increased risk of HF with gliptin usage 27 .…”
Section: Discussionmentioning
confidence: 92%
“…In the SAVOR-TIMI 53 study, saxagliptin usage was associated with decreased NT-proBNP levels (4 vs. 10 pg/mL in the placebo group; p  = 0.001) 20 . In the VIVIDD Trial, diabetic patients taking vildagliptin had lower BNP levels (28 vs. 14% in the placebo group) relative to baseline at 52 weeks 21 . On the other hand, acute treatment with linagliptin does not alter the plasma concentration of BNP and NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these reassuring results, some concerns have been raised regarding adverse events from the novel drugs, such as heart failure and pancreatitis for the DPP‐4 inhibitors, and sporadic cases of ketoacidosis for SGLT2 inhibitors . The relationship of DPP‐4 inhibitors with increased risks of hospitalization for heart failure has not yet been resolved; however, the results of another observational study and a meta‐analysis are not consistent with this finding …”
Section: Discussionmentioning
confidence: 99%
“…19,36 The beneficial associations of lowered CVD and mortality risks in the present study should also be interpreted in the context of a T2D population with a lower CVD burden at baseline compared with the clinical randomized trial. 17 Notwithstanding these reassuring results, some concerns have been raised regarding adverse events from the novel drugs, such as heart failure 44 and pancreatitis for the DPP-4 inhibitors, 45 and sporadic cases of ketoacidosis for SGLT2 inhibitors. 46 The relationship of DPP-4 inhibitors with increased risks of hospitalization for heart failure has not yet been resolved; however, the results of another observational study and a meta-analysis are not consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation